STRUKTUR KOMUNITAS MIKROARTHROPODA BRYOFAUNA EPIFIT DI ZONA TROPIK GUNUNG UNGARAN, JAWA TENGAH - Rina Eka Yuniarti; Rully Rahadian; Lilih Khotim Perwati (Jurnal Akademika Biologi, 2013)
Mount Ungaran has various diversity of flora, including bryophytes. Epiphytic bryophytes are the habitat of bryofauna most of them are  microarthropods. The objective of this research was to determine community structure of epiphytic bryofauna in tropical zone of Mount Ungaran. This research was conducted in tropical zone of Mount Ungaran at three different  altitudes. The sampling methods was using square plots. Bryophytes were collected in plots 10x10 cm on tree trunks. Furthermore, the specimens were extracted using Barlese funnel at Laboratory of Ecology and Biosistematics, Department of Biology, Diponegoro University up to seven days. The results shows there are 5 classes of 16 orders and 30 sub orders/families. The most diverse of epiphytic bryofauna found at altitude 980 m asl and 1100 m asl (H’= 2,30), while the lowest at 750 m asl (H’= 1,87). Order of Acarina is consistantly found dominant in all altitudes. Meanwhile, at 1100 m asl the order of Thysanopera has also high abundant or dominant. Keywords : community structure, epiphytic bryophytes, bryofauna, tropic zone.